Theta and beta oscillatory dynamics in the dentate gyrus reveal a shift in network processing state during cue encounters - Rangel, Lara M.; Chiba, Andrea A.; Quinn, Laleh K. (Frontiers in Systems Neuroscience, 2015)
The hippocampus is an important structure for learning and memory processes, and has strong rhythmic activity. Although a large amount of research has been dedicated towards understanding the rhythmic activity in the hippocampus during exploratory behaviors, specifically in the theta (5-10 Hz) frequency range, few studies have examined the temporal interplay of theta and other frequencies during the presentation of meaningful cues. We obtained in vivo electrophysiological recordings of local field potentials (LFP) in the dentate gyrus (DG) of the hippocampus as rats performed three different associative learning tasks. In each task, cue presentations elicited pronounced decrements in theta amplitude in conjunction with increases in beta (15-30Hz) amplitude. These changes were often transient but were sustained from the onset of cue encounters until the occurrence of a reward outcome. This oscillatory profile shifted in time to precede cue encounters over the course of the session, and was not present during similar behavior in the absence of task relevant stimuli. The observed decreases in theta amplitude and increases in beta amplitude in the dentate gyrus may thus reflect a shift in processing state that occurs when encountering meaningful cues.